2023
DOI: 10.1038/s41467-023-36658-y
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical amino acids as doubly bio-orthogonal handles for one-pot preparation of protein multiconjugates

Abstract: Genetic encoding of noncanonical amino acid (ncAA) for site-specific protein modification has been widely applied for many biological and therapeutic applications. To efficiently prepare homogeneous protein multiconjugates, we design two encodable noncanonical amino acids (ncAAs), 4-(6-(3-azidopropyl)-s-tetrazin-3-yl) phenylalanine (pTAF) and 3-(6-(3-azidopropyl)-s-tetrazin-3-yl) phenylalanine (mTAF), containing mutually orthogonal and bioorthogonal azide and tetrazine reaction handles. Recombinant proteins an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…This is in contrast to the majority of previous studies, which have employed ncAAs as “molecular handles” to facilitate the development of antibody-drug conjugates through click chemistry reactions, utilizing biorthogonal functional group such as azides. 4 , 5 , 6
Figure 1 Schematic describing applications of AAV engineering with ncAAs, including that described by Chang et al., versus historical engineering strategies focused on bioconjugation
…”
Section: Main Textmentioning
confidence: 99%
“…This is in contrast to the majority of previous studies, which have employed ncAAs as “molecular handles” to facilitate the development of antibody-drug conjugates through click chemistry reactions, utilizing biorthogonal functional group such as azides. 4 , 5 , 6
Figure 1 Schematic describing applications of AAV engineering with ncAAs, including that described by Chang et al., versus historical engineering strategies focused on bioconjugation
…”
Section: Main Textmentioning
confidence: 99%
“…In addition, the tissue penetrance of NIRF is considerably high. Bio-orthogonal chemistry has been used for NIRF imaging via several strategies: (1) incorporation of noncanonical amino acids (ncAAs) with alkyne or azide tags that can be conjugated with a fluorophore via bio-orthogonal reactions; (2) pretargeting that uses a molecule with a clickable tag to bind to the target of interest; (3) incorporation of clickable tags into glycans and lipids. The ncAA strategy has been widely used for cell imaging, and the pretargeting and glycan/lipid tagging strategies have been used for in vivo animal imaging.…”
Section: In Vivo Imaging With Bio-orthogonal Ligationmentioning
confidence: 99%
“…Remarkably, Wang et al recently demonstrated that it was feasible to have two orthogonal tags in one ncAA. In this study, they demonstrated that 4-(6-(3-azidopropyl)-s-tetrazin-3-yl) phenylalanine (pTAF) and 3-(6-(3-azidopropyl)-s-tetrazin-3-yl) phenylalanine (mTAF) could be incorporated into recombinant proteins and antibody fragments . This method could enable combinations of commercially available fluorophores, radioisotopes, poly­(ethylene glycol) (PEG), and drugs in a plug-and-play manner in one pot.…”
Section: In Vivo Imaging With Bio-orthogonal Ligationmentioning
confidence: 99%
“…[46] (b) Schematic of dual labeling of HER2-(scFv) antibody with FITC-tagged TCO and CY5-tagged DBCO via IEDDA and SPAAC reactions, respectively. [47] (c) Functionalization of Trastuzumab-Im10-TAMRA conjugate and bioorthogonal cleavage induced by cyclooctyne B. [48] Recently, Yang and Liu showed double labeling of antibodies by incorporating clickable azide and Tz handles into multiple non-canonical amino acids to carry out azide-cyclooctyne cycloaddition.…”
Section: Biomolecule Functionalizationmentioning
confidence: 99%
“…Yang and Liu introduced another design strategy for the preparation of homogeneous protein multiconjugates using two genetically encodable ncAAs: 4-(6-(3-azidopropyl)-s-tetrazin-3-yl) phenylalanine (pTAF) and 3-(6-(3-azidopropyl)-s-tetrazin-3-yl) phenylalanine (mTAF). [47] These azide and tetrazine containing ncAAs participated in IEDDA as well as SPAAC reactions in a single reaction vessel without interfering with each other (Figure 6b). They demonstrated that recombinant proteins and antibody (Her2) fragments containing the TAFs could be easily functionalized in one-pot reactions with commercially available fluorophores, radioisotopes, PEGs, and drugs, enabling the evaluation of tumor diagnosis, imageguided surgery, and targeted therapy in mouse models.…”
Section: Biomolecule Functionalizationmentioning
confidence: 99%